Affective symptoms and the overactive bladder — A systematic review - Vrijens, Desiree; Drossaerts, Jamie; van Koeveringe, Gommert; Van Kerrebroeck, Philip; van Os, Jim; Leue, Carsten (Journal of psychosomatic research, 2015)
Overactive bladder syndrome (OAB) is characterised by urgency symptoms, with or without urgency incontinence, usually with frequency and nocturia. Although literature suggest an association between OAB, depression and anxiety, no systematic review has been presented. Systematically review the literature on the association of affective conditions with OAB. Systematic review according to the PRISMA guidelines. This review is registered in the PROSPERO register (CRD4201400664). Forty-three articles were included, describing more than 80,000 subjects. Depression and OAB were positively associated in 26 studies, anxiety and OAB in 6 studies. Longitudinal studies reported: a) OAB subjects who developed depression/anxiety or b) depressed/anxious subjects developing OAB, or c) both. The quality of evidence in studies reporting an association between the co-occurrence of OAB and depression was rated level 3 in accordance with the GRADE framework. Evidence reporting on the co-occurrence of anxiety and OAB was rated GRADE level 2. Longitudinal associations between new onset of OAB in depressive subjects was GRADE level 2. Evidence reporting association of OAB with anxiety in longitudinal studies was of GRADE level 1. To our knowledge, this systematic review is the first to give a comprehensive qualitative overview on the association between OAB and affective symptoms. Many evaluated studies failed to note longitudinal changes and lacked evidence of causality. Still, results revealed an association between OAB and affective symptoms and there is evidence for new onset of OAB in depressive subjects, but further research is necessary to examine the strength of the effect. •The association between affective symptoms and overactive bladder was reviewed.•GRADE strength of evidence was determined per direction of possible association.•An association between affective symptoms and overactive bladder exists.•There is evidence for new onset of overactive bladder in depressive subjects.•The causal relationship remains to be elaborated.